Production potential of baby corn (Zea mays) on raised bed in waterlogged lowland rice fallow in North East India - PANWAR, A S; SHIVAY, Y S (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during rainy (Kharif) season of 2008-09 and 2009-10 at research farm of ICAR-Research Complex of NEH Region of Umiam, Meghalaya, to study the production potential of baby corn (Zea mays L.) as influenced by raised bed height in waterlogged low land area and nitrogen levels. Taller plants with more number of leaves were recorded with 50 cm height of raised bed. The days to harvest initiation and harvest duration were more at 50 cm height of raised bed. The barrenness in baby corn was also comparatively lesser with 50 cm height of raised bed. The maximum baby corn and fodder yield was recorded with 50 cm height of raised bed, which were 11.3 and 10.7% higher than 40 cm height of raised bed. Further, decrease in height of raised bed up to 30 and 20 cm markedly reduced babycorn yield as compared to 50 cm height of raised bed. The nitrogen content and uptake, protein yield, nitrogen use efficiency and economical parameters were also higher at 50 cm height of raised bed. Increasing nitrogen level produced taller plants with more number of leaves. The harvest initiation decreased by 4 days while harvest duration was increased by 4 days with 120 kg N/ha. The barrenness declined with increasing nitrogen levels. The highest baby corn yield, nitrogen uptake and protein yield were recorded with 80 kg N/ha. Increasing nitrogen levels progressively reduced agronomic N use efficiency and physiological efficiency of nitrogen, but apparent recovery increased up to 80 kg N/ha. The gross, net return and benefit: cost ratio were higher with 80 kg N/ha. Therefore, for getting higher yield and net return, the baby corn should be grown at 50 cm height above the moisture level on raised bed and fertilized at the rate of 80 kg N/ha.